While the city sleeps: a history of pistoleros, policemen, and the crime beat in Buenos Aires before Perón - Caimari, Lila M. (Violence in Latin American history, 2017)
Pistoleros -- Languages of crime -- Order and the city -- Detecting disorder -- The places of disorder -- While the city sleeps : police and social imagination